Report on the 2013 national cholelithiasis survey in Japan. (18th January 2015) - Tazuma, Susumu; Kanno, Keishi; Kubota, Keiichi; Tsuyuguchi, Toshio; Kamisawa, Terumi; Isayama, Hiroyuki; Nakagohri, Toshio; Inui, Kazuo; ,
Abstract: Background and aims: The Academic Committee of the Japan Biliary Association conducted a national survey of cholelithiasis and analyzed its current management centering on epidemiology. Methods: To allow comparison with previous results, a prospective survey was performed on the treatment of cholelithiasis during the month of August 2013, using the same questionnaire as that used for the 1997 Cholelithiasis Survey Project by the Japan Biliary Association. A personal questionnaire was sent to 71 institutions, and 612 individual survey sheets were collected from 56 institutions as treated during August 2013. Results and conclusions: Compared with the results obtained in 1997, the gender ratio was reversed in 2013 with male predominance. There were increases in the mean age, asymptomatic ratio, use of magnetic resonance cholangiopantreatography for diagnosis, and cholesterol stone type was also increased. Laparoscopic cholecystectomy was performed for 79.8% of gallbladder stones, and treatment of common bile duct stones generally involved endoscopic procedures, among which endoscopic sphincterotomy (EST) was performed more often compared with endoscopic papillary balloon dilation (EPBD), suggesting that EST is the mainstream treatment for common bile duct stones.